A rapid review of patient-reported outcomes investigated in the context of advanced renal cell cancer or advanced hepatocellular cancer. (April 2023) - Diez de los Rios de la Serna, Celia; Kotronoulas, Grigorios; Drury, Amanda; Oldenmenger, Wendy; Kelly, Daniel
Abstract: Background: Patient-reported outcomes (PROs) are key indicators of health status and functioning, coming directly from the patient. Comprehensive monitoring of PROs enables implementation of person-centred care. Currently, the PROs that patients with advanced renal cell carcinoma (RCC) or hepatocellular carcinoma (HCC) consider of greatest importance remains unknown. Methods: A rapid literature review was carried out to identify PROs commonly reported in clinical studies of patients with advanced RCC/HCC. We searched MEDLINE, CINAHL & PsycInfo for relevant peer-reviewed publications in the period from 2000 to 2021. Pre-specified selection criteria were applied to all retrieved records. Findings were integrated into a narrative synthesis. Results: Eighty-one studies met our selection criteria and were retained. Most research was on advanced RCC (n = 64, 79%); 46 studies (57%) were drug trials. Only twenty-six studies (32%) employed PROs as their primary endpoint. Most PROs concerned physical symptoms (45% RCC, 54% HCC) and emotional wellbeing (19% RCC, 16% HCC). The most common outcome measured was quality of life (65% of the total), followed by fatigue (62%) and pain (54%). Whether selection of these PROs was patient-driven was not reported. Conclusions: A wide range of PROs were assessed. Deficits in PROs often cause patients to seek out help; however, which PROs matter the most to people with advanced RCC/HCC must be further clarified. Targeting, monitoring, and responding to the 'right' PROs can enhance provision of person-centred care in advanced RCC/HCC and augment the clinical efficacy of established and emerging targeted therapies. Highlights: We explored what PROs are commonly reported in advanced renal or liver cancer. Quality of life and physical symptoms were the most frequently assessed PROs. Whether selection of these PROs was patient-driven was not reported. Clinicians must address the 'right' PROs for person-centred care to be enhanced.